Characterizations of Integral Type for Weighted Classes of Analytic Banach Function Spaces. (28th January 2022) - Shammaky, Amnah E.; Ahmed, A. El-Sayed
Abstract : The aim of this study is to give some new definitions of Banach spaces of holomorphic functions. Some holomorphic characterizations of integral type for some classes of Banach spaces of holomorphic functions are established in the unit disc U .